2009
DOI: 10.1017/s113874160000161x
|View full text |Cite
|
Sign up to set email alerts
|

Love and Emotional Well-being in People with Intellectual Disabilities

Abstract: Love has been a recurrent topic throughout history, and especially, literature. Moreover, there is generalized agreement about its relevance for health emotional well-being, and quality of life. This study was carried out with a sample of 376 persons with ID. The goals of the work were to analyze a theoretical model of love in people with intellectual disabilities by means of the methodology of structural equations, and to analyze their perception of love and of amorous relations with regard to other aspects s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 45 publications
2
19
0
3
Order By: Relevance
“…This interference created conflict and was consistent with findings in other studies [6,19]. Arias et al [20] also found that emotional well being significantly correlated with less family interference and a higher capacity of self-determinism in persons with intellectual disabilities.…”
Section: Discussionsupporting
confidence: 90%
“…This interference created conflict and was consistent with findings in other studies [6,19]. Arias et al [20] also found that emotional well being significantly correlated with less family interference and a higher capacity of self-determinism in persons with intellectual disabilities.…”
Section: Discussionsupporting
confidence: 90%
“…The commitment component refers to the cognitive decision to stay in the relationship long term. The conceptualization of triangular love theory (Sternberg, 1986(Sternberg, , 1997 has been widely adopted by many contemporary researchers to measure interpersonal romantic love (Aloni and Bernieri, 2004;Arias et al, 2009;Barelds and Barelds-Dijkstra, 2007;Bauermeister et al, 2011;Engel et al, 2002;Zeidner and Kaluda, 2008). Some researchers have extended the triangular love scale to measure consumers' love for brands, products, or firms (Albert and Valette-Florence, 2010;Jin and Jia, 2009;Yim et al, 2008), as well as people's religious love of God (Beck, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The participants were asked to recall their love relationships with their intimate partners for the time near the last Valentine's Day and to indicate their agreement on these measurement items with a five-point Likert scale. The triangular love scale has been widely used to measure interpersonal romantic love (Aloni and Bernieri, 2004;Arias et al, 2009;Barelds and Barelds-Dijkstra, 2007;Bauermeister et al, 2011;Engel et al, 2002;Zeidner and Kaluda, 2008) and has been proven valid for contemporary romantic Table 1. The statements and reliabilities of the scale items used in a study to examine the development stage of participants' romantic relationship in terms of rapport, self-revelation, mutual dependency, and personality need fulfillment via a consumer survey conducted in Taipei, Taichung, and Kaohsiung, Taiwan from 22 Apr.…”
Section: Samplingmentioning
confidence: 99%
“…Sua medida, a ETA, vem sendo empregada em várias pesquisas sobre o tema (Arias, Ovejero, & Morentin, 2009;Yela, 2000;Yela & Sangrador, 2003).…”
unclassified
“…Em busca realizada nas bases de dados da Biblioteca Virtual em Saúde (BVS Psicologia, 2009), incluindo como palavras-chave amor, tetrangular e escala, não foi encontrado qualquer relato de pesquisa em que essa medida tenha sido empregada, portanto, considerando esse fato e o aspecto de essa medida introduzir uma contribuição importante no estudo do amor, decidiu-se adaptá-la ao contexto brasileiro. Esclarece-se, em decorrência, que a definição de amor assumida neste estudo abarca um sentimento interpessoal positivo e multifacetado, que se expressa por meio de quatro dimensões: compromisso, intimidade, paixão erótica e paixão romântica (Arias et al, 2009;Yela, 2000Yela, , 2006Yela & Sangrador, 2003). A expressão absoluta de amor, coerente com a abordagem de R. Sternberg em que se baseou essa medida, representaria a maximização dos quatro componentes, porém reconhece-se que nem sempre isso é possível, pois configuraria diferentes modalidades de amar (Sternberg, 1988(Sternberg, , 1998.…”
unclassified